Barley grain protein is influenced by genotype, environment, and nitrogen management and is the major driver of malting quality. Issue 1 (9th November 2022) - Halstead, Margaret; Morrissy, Campbell; Fisk, Scott; Fox, Glen; Hayes, Patrick; Carrijo, Daniela
Abstract: Malted barley ( Hordeum vulgare ) is a crucial component of beer, and it has been established that barley genotype has an effect on malting quality and beer flavor. This study extends this exploration by evaluating the effects of genotype, environment, and management on malting quality. Five fall‐planted malting barley lines were grown in three locations, each representing a distinct growing environment in the Pacific Northwest (United States), and under nitrogen (N) treatments: control (N1) and N application at heading in addition to the control (N2). Genotype × location interactions were observed for all agronomic (yield, test weight) and grain quality metrics (grain protein, plumpness), and N treatment × genotype interactions were observed for grain protein and plumpness. Overall, N2 increased grain protein, without exceeding specifications, by almost 1% point. Based on random forest analysis, the major driver of all‐malt index score was grain protein, followed by peak gelatinization temperature, germination energy, and water sensitivity. Still, over 70% of variation in all‐malt index score was unexplained, which is likely due to genotype and location differences, as indicated by principal component analysis. This research confirms the agronomic potential of fall‐planted malting barley in the Pacific Northwest and, although micromalted samples did not meet industry specifications, trends were identified that indicate the potential for these varieties at these locations. This research also demonstrates the potential of N management to fine‐tune malting quality through grain protein, and that malting quality is influenced by genotype and environment, though many of the specific drivers remain unknown. Core Ideas: Five barley genotypes were evaluated in three locations under two N treatments. Nitrogen applied at heading can be used to fine‐tune barley grain protein. Grain protein is the major driver of malting quality scores. Genotype and environment influence grain protein and other drivers of malting quality.